MODELLING INFLATION DYNAMICS: A STATISTICAL INVESTIGATION OF FUEL PRICE, MONEY SUPPLY, AND EXCHANGE RATE - Elijah, Babatunde Sunday (FUDMA Journal of Sciences, 2026)
Persistent inflation remains a central challenge in Nigeria’s macroeconomic landscape, raising questions about the true drivers of price instability in recent years. This study explores the interconnected roles of money supply (M2), fuel price, and exchange rate (EXR) in explaining inflationary dynamics using monthly data from January 2020 to December 2024. Leveraging the Vector Error Correction Model (VECM), the analysis captures both short-run fluctuations and long-run equilibrium relationships. Results from the Johansen cointegration test reveal two stable long-run relationships, particularly highlighting the strong link between inflation and exchange rate movements. Granger causality analysis identifies exchange rate and money supply as significant short-run predictors of inflation, while impulse response functions confirm that exchange rate shocks produce the most persistent inflationary effects. Interestingly, fuel price exerts limited short-term influence on inflation, suggesting the moderating role of domestic price controls. Residual diagnostic tests validate the model’s robustness. Overall, the findings underscore the critical importance of exchange rate management and monetary discipline in curbing inflation, offering timely insights for policymakers navigating Nigeria’s post-subsidy and post-pandemic economic recovery.